Cartera de crédito vencida en la Empresa Yamaha de la ciudad de Babahoyo durante el periodo 2023. - García Laborda, Annie Zoraida (2024)
In this case study, the objective is to examine the overdue loan portfolio of the company Yamaha in the city of Babahoyo during the period 2023 in order to understand the importance of the portfolio in companies. It is observed that the Yamaha company has an inefficient control with respect to accounts receivable, causing liquidity, especially the cash ratio, to deteriorate because there are no strict policies with respect to payments to be made by customers. Likewise, financial analysis techniques were used to help determine the incidence of the credit portfolio with respect to liquidity. In addition, an explanatory and descriptive methodology was used, determined with a mixed approach, since it allowed to collect all the necessary information to have a general vision of the research topic.